One Class, One Pot, One Tree as a Sustainability Design Strategy in Environmental Management at SMP Negeri 1 Warureja - Ismiyati Hanum; Didit Widiatmoko Soewardikoen; Irwan Sudarisman (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Environmental issues have become a global concern that requires serious attention, including in the education sector. This study aims to evaluate the